Heart, life, music [large type] - Chesney, Kenny; Gleason, Holly (William Morrow Large Print, an imprint of HarperCollinsPublishers, 2025)
"In college, Country Music Hall of Fame member Kenny Chesney found himself on a barstool with a guitar and an unexpected connectionbetween people, life, and songs. His heart caught fire. With Nashville's vibrant creative scene, characters, legends, and places now long gone from the city he encountered in those early days, Chesney explores the quest to find himself as an artist and a man, as well as a sense of home anywhere there's an ocean. These are the stories of the unlikely game changer who became the sound of coming of age in the 21st century, made friends with his heroes, rocked stadiums, and founded a No Shoes Nation"--